Prevalence of Metabolic Syndrome in Chinese Patients With Erythrodermic Psoriasis: A Case-Control Study - Ma, An-ran; Liu, Fang; Wang, Runnan; Lin, Lanmei; Wang, Yilun; Li, Qunyi; Lu, Xiaonian; Du, Juan (Frontiers in Endocrinology, 2021)
Erythroderma psoriasis (EP) is a rare and severe form of psoriasis, which is a chronic inflammatory skin disease that usually occurs simultaneously with cardiovascular disease (CVD). Metabolic syndrome (MetS) is a significant precursor of CVD. This study was to investigate the association between EP and MetS in the Chinese population. We conducted a retrospective study on 86 consecutive patients with EP and 100 healthy controls from Huashan Hospital between 2013 and 2018. Demographic, biochemical parameters for MetS, and other relevant data including the severity of EP, family history of EP, age of onset, and treatment history involved in those individuals were recorded. The prevalence of MetS in erythrodermic psoriatic patients was 88.37%, which was significantly higher than that of controls (P <0.0001). Erythrodermic psoriatic patients also had a higher prevalence of MetS components, including abdominal obesity, dyslipidemia and hypertension, whereas hyperglycemia was similar. Adjusted for confounding factors, MetS, abdominal obesity, hypertension, smoking and alcohol use were positive independent predictors of EP (odds ratio >1, P < 0.05). The area under the receiver operating characteristic curve calculated from determined risk factors for predicting the EP's incidence was 0.924 (95% CI 0.900-0.967). There was no correlation between the severity of EP and the prevalence of MetS. Compared with patients with mild EP, patients with moderate-to-severe EP had higher body mass index, waist circumstance and blood pressure (P < 0.05). We concluded that the prevalence of MetS and its components was higher in patients with EP. MetS an independent predictor of EP, which can favor CVD and should be encouraged to correct these cardiovascular risk factors aggressively for managing EP.